O imaginário dos professores de música acerca do cotidiano musical dos jovens: um estudo no contexto das escolas integrais de Barueri, SP - Santos, Samuel Cintra [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
My experience with continuing formation of Music teachers in the city of Barueri, in São Paulo state, prompted me to investigate the imagery these teachers have about the relationship that young students have with music in their everyday experiences and how this would imply the work teaching in school. Teachers of Music, who became partners in this work, act in Secondary School in the municipal public education of Barueri; the young people are students who attend these schools from sixth to nineth grade. The study is based on a socio-cultural approach to music education and epistemologically fits the paradigm of complexity according to Edgar Morin. I assume as a theoretical framework for analyzing and interpreting the notion of imagery according to Maffesoli. In the research, I followed a qualitative approach and resorted to a document analysis, open and informal interviews with teachers and observations of teachers’ performance in curricular music lessons and school projects. The results of the investigation were a survey description and categorization of eight personal imagery of Music teachers; the appointment of a plausible hypothesis that the imagery of the Music teacher about the daily musical lives of students imply teachers actions with young people in school; the indicative that the same imagery does not necessarily generate homogeneous actions on teachers at the school of music; and the observation that, beyond the imagery, there are other key factors that also influence the Music teacher practices in school

Minha experiência com a formação continuada de professores de Música no município de Barueri, SP, instigou-me a investigar que imaginário esses docentes teriam a respeito da relação que os jovens estudantes estabelecem com a música em suas experiências cotidianas e se isso implicaria no seu trabalho pedagógico na escola. Os professores de Música, que se tornaram parceiros neste trabalho, atuam no Ensino Fundamental II em escolas de período integral da rede pública municipal de educação de Barueri; os jovens são estudantes que frequentam essas escolas de 6º a 9º ano. O estudo se assenta em uma abordagem sociocultural da Educação Musical e se insere epistemologicamente no paradigma da complexidade segundo Edgar Morin. Assumo como referencial teórico de análise e interpretação a noção de imaginário segundo Michel Maffesoli. Na pesquisa segui a abordagem qualitativa e recorri a análise de documentos, entrevistas abertas e informais com os professores e observações da atuação docente em aulas curriculares de música e nos projetos escolares. Os resultados da investigação foram o levantamento, descrição e categorização de oito imaginários dos professores de Música; o apontamento como plausível da hipótese de que os imaginários do professor de Música acerca do cotidiano musical dos estudantes implicam suas ações com os jovens na escola; o indicativo de que um mesmo imaginário não gera, necessariamente, ações homogêneas nos professores de Música na escola; e a observação de que, além dos imaginários, existem outros fatores-chave que também influenciam as práticas do professor de Música na escola
Keywords: Musica - Instrução e estudo; Professores de musica; Musica na educação; Imaginario; Music - Instruction and study; São Paulo (Estado)